1998
DOI: 10.1161/01.atv.18.4.650
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Withdrawal–Induced Change in Lipoprotein(a)

Abstract: Abstract-Lipoprotein(a) [Lp(a)] is an important risk factor for cardiovascular disease. Alcohol is one of the few nongenetic factors that lower Lp(a) levels, but the metabolic mechanisms of this action are unknown. Alcohol inhibits the growth hormone (GH)/insulin-like growth factor-I (IGF-I) axis. Alcohol might also affect IGF-binding protein-1 (IGFBP-1), which is an acute inhibitor of IGF-I. We studied how alcohol withdrawal affects Lp(a) levels and the GH/IGF-I/IGFBP-1 axis. Male alcohol abusers (nϭ27; 20 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…36 Serum GH levels were also measured in the present study and these levels were similar in teetotalers and heavy drinkers (1.53Ϯ5.50 versus 1.76Ϯ3.37 pmol/L, NS). These present data, however, do not rule out a role for GH or insulin-like growth factor-binding protein-1 22 in mediating the inverse relation between alcohol intake and Lp(a) levels, as, in our study, blood was drawn during daytime and insulin-like growth factor-binding protein-1 was not measured.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…36 Serum GH levels were also measured in the present study and these levels were similar in teetotalers and heavy drinkers (1.53Ϯ5.50 versus 1.76Ϯ3.37 pmol/L, NS). These present data, however, do not rule out a role for GH or insulin-like growth factor-binding protein-1 22 in mediating the inverse relation between alcohol intake and Lp(a) levels, as, in our study, blood was drawn during daytime and insulin-like growth factor-binding protein-1 was not measured.…”
Section: Discussioncontrasting
confidence: 89%
“…21 The mechanism by which alcohol withdrawal is associated with an increase in Lp(a) levels is poorly understood and may implicate changes in insulin-like growth factor-binding protein-1. 22 However, whether the inverse association between alcohol intake and serum Lp(a) levels holds true for the entire size spectrum of apo(a) isoforms and whether it is because of altered synthetic function of the liver or changes in sex hormone status has not been investigated. Finally, the association between alcohol intake and Lp(a) levels in individuals of African descent has only been documented incompletely.…”
mentioning
confidence: 99%
“…Also sensitivity analyses, which were conducted to reduce the risk of information bias by replacing self-reported alcohol consumption by objective markers of alcohol misuse, did not affect the major findings. Intervention studies demonstrated that both alcohol withdrawal (36) and an optimized diet with low content of total fat and refined carbohydrates (37) increases serum IGF1 levels in treated subjects. Thus, with respect to serum IGF1 levels and probably also with respect to the risk of metabolic syndrome, the cause of hepatic steatosis might be less important than hepatic steatosis itself.…”
Section: Ultrasoundkaltk Ultrasoundkaltc Ultrasoundcaltk Ultrasoundcaltcmentioning
confidence: 99%
“…The chronic consumption of ethanol results in a marked decrease of the Lp(a) concentration which is dose-dependent and has no relationship with the size polymorphism of apo(a) [2,156,157]. Vice versa the Lp(a) concentration rises again after termination or reduction of alcohol consumption [158][159][160]. The mechanism of action is not completely known.…”
Section: Influence Of Nutrition and Life-style On Lp(a) Plasma Concenmentioning
confidence: 99%
“…The mechanism of action is not completely known. It is discussed that it involves insulin-like growth factor (IGF)-binding protein [2,159].…”
Section: Influence Of Nutrition and Life-style On Lp(a) Plasma Concenmentioning
confidence: 99%